The tribological properties of friction pairs after running rollers with stabilization of working efforts - Бутаков, Б.И.; Артюх, В.А. (Problems of Tribology, 2014)
Study on distribution of hardness measurement by depth indicated that after folding shaft roller using the device with the stabilization efforts of spinning, a fairly homogenous in structure and properties of the surface layer, which ensures the quality of the material throughout the resource work details. After testing for wear in liners, working in tandem with the broken specimen is a great wear resistance compared to the ground.